ANALISIS PROSPEK PENGEMBANGAN KUNJUNGAN WISATA PANTAI KABUPATEN TAKALAR - Syachbrani, Warka; -, Bahrun (Jurnal Ilmiah Ecosystem, 2020)
This study aims to analyze the development of tourism objects in increasing tourist visits and to analyze the supporting and inhibiting factors in developing the tourism object of Topejawa Beach, Takalar Regency. This research was conducted for 1 year, from January to December 2020 at the Takalar Regency Tourism Office and Topejawa Beach Tourism Object, Takalar Regency. This study uses primary and secondary data. The data collection techniques used were observation and interviews. The population of this study were employees of the Takalar Regency Tourism Office and Topejawa Beach Tourist Attractions. The sample in this study was taken 100 people (tourist visitors). The sample is taken proportionally with proportional random sampling method. Data processing is done by using the method of observation, interviews and documentation. The analysis used is quantitative and qualitative data analysis. The analytical method used is trend analysis and time series analysis.